Emanating Change Fragments of Micro-Empowerment Among Women Leaders in Mindanao Philippines - Baena, Xandelyn Racel; Langbid-Roda, Rose; Otano, Jed; Derogongan, Rohane; Reyes, John Leandro (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
Significant efforts have been undertaken to address the challenges in Mindanao. Given the complexity of issues in the region, a top-down approach must be complemented by grassroots-level initiatives. In this context, micro-empowerment is key to fostering positive community transformation. This article explores the motivations and work of twelve (12) women leaders in Mindanao who have advanced community empowerment through education, micro- entrepreneurship, and peace-building initiatives. These efforts have amplified marginalized voices and enhanced the visibility of women’s participation in addressing issues of peace and social justice, contributing to the broader cause of women’s empowerment in Mindanao. Moreover, their community engagement has fostered personal growth, offering a nuanced understanding of empowerment. Using narrative analysis, the study evaluates the motivations and fundamental practices behind these leaders’ grassroots efforts. Findings reveal that the women’s activism arises from intersecting factors such as contextual influences, ingrained social activities, and experiences of marginalization, which shape their unique perspectives on community concerns. Their activism is not coincidental, but a reflexive response to their lived experiences, inspiring them to drive change. By integrating the concepts of situated knowledges and intersectionality, the study highlights how these women’s consciousness and worldviews have informed their community engagement, transforming personal narratives into political action. By amplifying women’s narratives, the study underscores the importance of inclusive narratives in addressing gender inequalities, aligning with the United Nations Sustainable Goals focused on gender equality and women’s empowerment.